Flexible hoses, end fittings and sockets for gas burning appliances. Specification for corrugated metallic flexible hoses, covers, end fittings and sockets for catering appliances burning 1st and 2nd family gases Part 2, (29th February 1988) - British Standards Institution,
No abstract available